PENGALAMAN KELUARGA DALAM MENGASUH BALITA STUNTING BALITA DI SAMBAS - Simanjuntak, Daddy Deo Gilbert Pamungkas; Rahmawati, Nadia; Mita, Mita (Tanjungpura Journal of Nursing Practice and Education, 2026)
Background: Stunting cases occur worldwide, with many toddlers in various countries experiencing stunting and chronic malnutrition. Data from the United Nations Children's Fund (UNICEF) in 2020 showed that 22% of all children globally, or approximately 149.2 million children, suffered from stunting. According to the Indonesian Nutritional Status Study (SSGI), the prevalence of stunted toddlers in Indonesia was 24.4% in 2021. In 2021, West Kalimantan ranked seventh nationally with a stunting prevalence rate among toddlers of 29.8%. Sambas Regency is one of the districts with the highest number of stunting cases in West Kalimantan, with as many as 5,500 stunted toddlers. Objective: To explore the experiences of families in caring for stunted toddlers in Sambas Regency. Methods: This research is a qualitative study using a phenomenological approach. Five participants were involved in this study, selected using purposive sampling. Data were collected through in-depth interviews. Results: The study identified seven themes: sources of information, feelings, challenges in child care, support for child care, difficulties related to children’s eating, food selection for children, and sources of water for consumption. Conclusion: Eating difficulties among children were found to be one of the main contributing factors to stunting in this study. Parenting style is a crucial factor in children's growth and development. It is essential to implement good parenting practices so that children receive adequate nutrition for optimal growth and to prevent stunting. A limitation of this study is that the researcher led the participants toward the options being asked and did not brief the research assistant before conducting interviews.